COMMON MISTAKES IN CONSTRUCTING QUESTIONS IN CONVERSATIONS - Fajar Rahmani, Eka; Ratna Puspita, Agustina (LPPM STBA Pontianak, 2018)
As a foreign language, English is hardly ever used in daily practice at schools. It is only spoken fluently and actively in certain international schools in Indonesia, such as British International School and Jakarta Multicultural School, in which the medium of instruction is English. Indonesian learners are not familiar in English, so that they use it passively. As a consequence, more learners make mistakes in speaking, especially when they are constructing questions in conversations. Accordingly, this study aims at analyzing the common mistakes produced by students in constructing questions. This study employs descriptive qualitative methodology in which the writer describes the results of the analysis that show learners do make mistakes in constructing questions in declarative, yes/no interrogative, alternative interrogatives, interrogatives, and double interrogative forms. It happens because they are not aware of the proper forms of questions, and also they do not practice English frequently. Therefore, mistakes appear due to these factors.